Effect of Condom Use on Per-act HSV-2 Transmission Risk in HIV-1, HSV-2-discordant Couples. (17th November 2015) - Magaret, Amalia S.; Mujugira, Andrew; Hughes, James P.; Lingappa, Jairam; Bukusi, Elizabeth A.; DeBruyn, Guy; Delany-Moretlwe, Sinead; Fife, Kenneth H.; Gray, Glenda E.; Kapiga, Saidi; Karita, Etienne; Mugo, Nelly R.; et al.
Abstract : Human immunodeficiency virus-discordant couples at risk for transmitting herpes simplex virus type 2 (HSV-2) were selected. Couples recorded sex, condom use, and were followed for HSV-2 transmission. Condoms were 96% effective at preventing HSV-2 transmission from men to women and 65% effective from women to men. Abstract: Background. The efficacy of condoms for protection against transmission of herpes simplex virus type 2 (HSV-2) has been examined in a variety of populations with different effect measures. Often the efficacy has been assessed as change in hazard of transmission with consistent vs inconsistent use, independent of the number of acts. Condom efficacy has not previously measured on a per-act basis. Methods. We examined the per-act HSV-2 transmission rates with and without condom use among 911 African HSV-2 and human immunodeficiency virus type 1 (HIV-1) serodiscordant couples followed for an average of 18 months in an HIV prevention study. Infectivity models were used to associate the log10 probability of HSV-2 transmission over monthly risk periods with reported numbers of protected and unprotected sex acts. Condom efficacy was computed as the proportionate reduction in transmission risk for protected relative to unprotected sex acts. Results. Transmission of HSV-2 occurred in 68 couples, including 17 with susceptible women and 51 with susceptible men. The highest rate of transmission was from men to women: 28.5 transmissions per 1000 unprotected sex acts. We found that condoms were differentially protective against HSV-2 transmission by sex; condom use reduced per-act risk of transmission from men to women by 96% ( P < .001) and marginally from women to men by 65% ( P = .060). Conclusions. Condoms are recommended as an effective preventive method for heterosexual transmission of HSV-2.